Internal Control System and Fraud Prevention in Nigerian Deposit Money Banks - Fabiyi, Olanrewaju Oluwatimileyin; Aregbesola, Olateju Dolapo; Wright, Olatunde; Omojola, Sunday Olusola; Kolawole, Peace Ebunoluwa (International Journal of Economics and Financial Issues, 2025)
Financial institutions worldwide have been characterized by high level of fraudulent activities arising from weaknesses in the internal control processes that have been put in place in the financial organizations to help achieve the set goals and objectives. This paper investigated the influence and effect of the internal control system on fraud prevention in Nigeria deposit money banks by testing selected components of the internal control system against fraud prevention in these institutions. The study made use of the survey design to obtain the data through a structured questionnaire administered to employees of selected deposit money banks in Nigeria. The result revealed that control environment (β = −0.181, P = 0.000) and information and communication (β = 0.964, P = 0.000), proxies of internal control system significantly influences fraud prevention while risk assessment (β = −0.123, P = 0.054) of internal control shows a negative impact on fraud prevention. The study concludes that information and communication of internal control as well as control activities of the internal control system significantly influences fraud prevention in the institutions while risk assessment does not show a positive effect on fraud prevention.